Oral health: How health promotion and disease prevention actions are carried out by professionals from the Oral Health Teams in the Family Health Strategy (Research, Society and Development, 2022)
In order to reduce the negative impacts of oral health problems, health promotion actions are carried out in Primary Care with dental health teams in the Unified Health System (SUS). From a preventive perspective, it is necessary for health promotion to be successful at a collective and individual level so that subjects have the necessary autonomy, prioritizing self-care, reducing the need for clinical interventions. This work aims to report how the promotion and prevention care has been carried out by the oral health teams of the Family Health strategy. To carry out the same, the Scielo database, PubMed and the Ministry of Health manuals were consulted as a reference. The Oral Health Teams have to carry out the same, the Scielo database, PubMed and the Ministry of Health manuals were consulted as a reference. The Oral Health Teams have responsibility at the local level for the consolidation of community actions and the restructuring of services in the area of Oral Health, which makes it necessary to advance in the development of educational practices during care in the SUS and the preparation of professionals so that there is training for better performance of the work.